Anaplastic lymphoma kinase (ALK) protein expressing lymphoma after liver transplantation: case report and literature review. Issue 11 (1st November 2002) - Costes-Martineau, V; Delfour, C; Obled, S; Lamant, L; Pageaux, G-P; Baldet, P; Blanc, P; Delsol, G
Abstract : Most post transplantation lymphoproliferative disorders (PTLDs) are Epstein-Barr virus (EBV) associated B cell proliferations. We report a case of aggressive anaplastic large cell lymphoma expressing the anaplastic lymphoma kinase (ALK) protein in a 58 year old man who had previously undergone liver transplantation. A definite diagnosis was not possible on histopathological examination. Immunostaining clearly showed a predominant population of small irregular lymphocytes, admixed with large cells strongly positive for CD30, epithelial membrane antigen, and the ALK protein. Neoplastic cells were of the T/cytotoxic phenotype. In situ hybridisation with EBV encoded early RNA probes showed only a few scattered positive non-neoplastic small lymphocytes. Polymerase chain reaction analysis of immunoglobulin and T cell receptor rearrangements was negative. The NPM–ALK fusion transcript associated with the t(2;5) translocation was detected by reverse transcription polymerase chain reaction. A review of the literature revealed 76 cases of T cell PTLD, showing a broad spectrum of morphological features and clinical behaviour. Most of these cases were EBV negative (61 of 76) and occurred after renal transplantation (48 of 76). To our knowledge, this is the first case of ALK positive lymphoma occurring in the setting of organ transplantation. This observation stresses the need for accurate immunostaining for diagnosing this rare, apparently aggressive, lymphoma in immunosuppressed patients.